If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -9) = 3 Reorder the terms: 4(-9 + x) = 3 (-9 * 4 + x * 4) = 3 (-36 + 4x) = 3 Solving -36 + 4x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 4x = 3 + 36 Combine like terms: -36 + 36 = 0 0 + 4x = 3 + 36 4x = 3 + 36 Combine like terms: 3 + 36 = 39 4x = 39 Divide each side by '4'. x = 9.75 Simplifying x = 9.75
| -5p=5/7 | | -8.3+4.7=d | | -3(-2+5r)+2r=-8r-14 | | 6(3-2n)= | | (-7x)+2x= | | -3.8x=-16.8-1.4x | | -3.8x=16.8-1.4x | | 2k=22 | | -5/4y+9/2=-3/8 | | (-7x)+2= | | 4x^2+(-2)+(-7x^2)+(-2x)+(-4)= | | 15x^2-39x+18=0 | | 2(d+3)+d=12solve | | -2/7/(-8/21) | | 1/8y-1/2=7/8 | | (-2x)+5x+x= | | 2n^2=11n+5 | | 2n^2=11x+5 | | 3x+(-5x)+x= | | -4.2/12 | | (n/2)/(3/8) | | 3x+(-9x)= | | -34-7b=-3(6b+4) | | (-2x)+(-x)= | | 35r=21r | | 3w+9= | | -4/7+y=-1/2 | | 8.7n-9.1=-18.1+4.2n | | (-3x)+x= | | 5x*2+5(6x*2-x)-3x= | | -2(3-2g)+4g=10solve | | tanx=0 |